Productivity and basic indicators of common bean (haricot) modern varieties suitability for mechanized harvesting - Olifirovych, S. (Interdepartmental Thematic Scientific Collection of Phytosanitary safety, 2024)
Goal. Investigation of plants height, a lower bean attachment height, 1000 seeds weight, ripening period duration, and productivity of common bean (haricot) modern varieties, depending on cultivating technological methods. Methods. Field method — to determine the plants height and grain crop capacity; laboratory one — to determine the basic elements of common bean plant crop structure; statistical — for mathematical data processing by variance analysis method. Results. All the six common (haricot) bean varieties investigated in the research, were bushy. However, the varieties Nata and Bukovynka showed the «chick-pea» (twisted) top appearance in years with excessive humidity. The variety Slavia was characterized by the lowest height of the lower bean attachment — 8.1—8.8 cm. Other researched varieties were more technologic. Particularly, the variety Galaktyka had the lower bean attachment height 10.1—10.6 cm, Bukovynka — 10.5—11.5, Nata — 10.5—11.8, Ros’ — 11.4—12.4 cm. The lower bean elevated location of the variety Otrada (12.9—13.5 cm) allows to minimize the losses during direct combine harvesting. All the varieties investigated by us had a medium-sized seed (from 201 tо 400 g). The smallest seed was in the variety Bukovynka — 204—212.6 g. The largest 1000 seeds weight was in the variety Galaktyka — 323.5—337.9 g. All the common bean vaieties researched in the experiment, except Galaktyka, exceeded the variety Bukovynka by grain yield. Thus, on the variant without seed inoculation and using potassium humate, the variety Galaktyka grain yield made 1.33 t/hа, which was by 34.5% less, compared to the variety Bukovynka. A complex use of inoculants and potassium humate provided a significant grain yield increase of the researched common bean varieties. The maximum yield increase in the research (0.27 t/hа or 11.0%) was obtained during pre-sowing seed inoculation and two foliar feedings with potassium humate of common bean stands of the variety Otrada. Conclusions. All the varieties researched in the experiment are bushy, and bushy with a «chick-pea» (twisted) top and suitable for direct combine harvesting. The maximum grain yield level was provided by the following varieties: Otrada — 2.72 t/ hа; Nata — 2.65 t/hа, and Ros’ — 2.54 t/hа, during seed inoculation with biologics Rhizoactive + Rootella, complete mineral fertilizer introduction in dosage N32Р32К32, and two foliar feedings with potassium humate.